THE SELF AS PREDICTOR OF EQUITY COMPARISON AND JOB SATISFACTION (1987)
Perhaps one of the most unresearched subjects is the impact of the self on employees' perceptions of and reactions to inequity (Locke, 1976; Mowday, 1979; Brockner, 1985). Therefore the purpose of this research is to investigate the influence of the self on equity comparisons and job satisfaction. The self variables in this study are the general and self; self-esteem, competence thema, ability and influence. Equity comparisons refer to: work-related aspects of the thema, ability and influence. (1) the degree of equity perceived relative to others (POOEQ) or the self outside the organization (PSOEQ),(2) the kind of comparative referents selected in making pay equity evaluations (e.g. self or others inside or outside the organization). Questionnaires were used to collect data from 550 employees from 11 banks (275 bank workers) and 6 ministries, (275 Government workers) in Ibadan. Sixty-six percent were males while thirty-four per cent of the respondents were females. Their average age was 39.9 years and their median educational level was high school certificate or its equivalent. Results of a series of hierarchical multiple regression analyses showed that as expected, competence thema and influence showed significant positive association with perceived self-outside and other-outside equity. Unexpectedly, self-esteem and ability showed negative relationship with perceived equity states. However, further analysis revealed that although both low self-esteem and ability groups made relatively more favourable evaluations, on the average, low and high self-esteem or ability groups all made equitable comparisons. Expectedly, the self variables (except ability) showed significant positive associations with job satisfaction. An interesting finding was that this self variable set accounted for 25% (P<.001) of the total variance in job satisfaction, with competence thema accounting for 16% (P<.001). This is remarkable considering the little attention the self variable has been given in previous studies. Also consistent with expectations, both POOEQ and PSOEQ showed significant positive relationships with job satisfaction. In addition, the results showed that the comparison of many job outcomes have cummulative effect. Individuals who feel relatively more disadvantaged on many job outcomes exhibit less satisfaction than those who feel more advantaged on many jobs. Also, employees who used few referents for pay equity evaluations tended to make more favourable equity comparisons than those who use multiple referents. A series of 2 x 2 ANOVA revealed that employees who used self referents for pay evaluations are those who exhibit higher self-esteem and influence than those who used other referents. Also, individuals who used outside referents scored higher on ability and self-esteem than those who used inside referents. Stepwise multiple discriminant analysis showed that the most important predictors of referents' selection were competence thema job tenure. Finally, path analysis results suggested that consistent with the proposed model of association, the self exerted direct influences on both perceived equity and job satisfaction, and an indirect influence on job satisfaction through relationships with perceived equity. It was concluded that in order to enhance employees' affective responses to work, organizations must strive to satisfy employees' implicit needs by providing rewards (motivation) which constantly give them ample opportunities to fulfill those perceived characteristics of the self.